Body shape and stable employment opportunity analysis of China's nonagricultural labor market - Ping Li; Xiaozhou Chen; Frank Stafford; Jinyun Ou (Elsevier, 2022)
Based on the integrated data of the China General Social Survey (CGSS) from 2010 to 2017, this study observes that body shape - being overweight or underweight - is important for labor market outcomes. Body shape significantly affects the employment opportunities of Chinese individuals, and this effect differs by gender and across the occupational hierarchy. Women face both slim premium and obesity penalty effects. Slim women, those with normal and lower but not excessively lower body weight, are more likely to gain long-term employment contracts in the labor market, while the opposite is observed for overweight individuals. The relationship between women's body shape and employment opportunities also varies by occupation. The obesity penalty is more pronounced in occupations with a higher International Socio-Economic Index (ISEI), while the slim premium is more evident in occupations with a low ISEI. The results suggest that the Chinese labor market is highly demanding regarding women's figures, while it is relatively tolerant of men's figures. By mechanism analysis, health capital is found to be the leading cause of the body shape effect. In addition, socialization is also a possible pathway of action. This paper has extended implications for the study of stature and employment stability, enriching the empirical research on labor market discrimination.